2023
DOI: 10.1021/acsami.3c07719
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-driven Supraparticle Synthesis by Self-Lubricating Colloidal Dispersion Microdrops

Jeongbin Heo,
Jaeseung Lee,
Wonmi Shim
et al.

Abstract: The surface-templated evaporation-driven (S-TED) method that uses liquid-repellent surfaces has attracted considerable attention for its use in fabricating supraparticles of defined shape, size, and porosity. However, challenges in achieving mass production have impeded the widespread adoption of the S-TED method. To overcome this limit, we introduce an evaporation-driven “multiple supraparticle” synthesis by drying arrays of self-lubricating colloidal dispersion microdrops. To facilitate this synthetic method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A similar study was reported for the droplets of a colloidal dispersion deposited on a superhydrophobic surface; evaporation and the absence of contact line pinning allowed the formation of supraparticles. 120–122 However, this method does not enable the formation of core–shell type supraparticles that make LMs a valuable tool for forming such complex materials.…”
Section: Lm-templated Materials Designmentioning
confidence: 99%
“…A similar study was reported for the droplets of a colloidal dispersion deposited on a superhydrophobic surface; evaporation and the absence of contact line pinning allowed the formation of supraparticles. 120–122 However, this method does not enable the formation of core–shell type supraparticles that make LMs a valuable tool for forming such complex materials.…”
Section: Lm-templated Materials Designmentioning
confidence: 99%
“…Evaporating sessile droplets over solid substrates is also an important geometry, which can be encountered in various applications like spray cooling, 4 chemical and biological assays, 5 medical diagnosis, 6 spreading of pesticides, 7 or material self-assembly. 8 In the past decades, such configuration witnessed an increased interest in the context of inkjet printing, 9 which has overcome the usual application of printing on paper 10 to become a cheap and versatile method for additive manufacturing, employed for flexible organic and inorganic electronics, 11 light-emitting devices, 12 pharmaceutical products, 13 biomaterials, 14 or filtration membranes. 15 From a fundamental point of view, the dynamics of evaporation of a liquid is an old problem 16 and has been the subject of intense experimental and modeling efforts for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the coatings start under the form of films of liquid suspensions spread over substrates, as for paints or lithium-ion batteries among other examples. Evaporating sessile droplets over solid substrates is also an important geometry, which can be encountered in various applications like spray cooling, chemical and biological assays, medical diagnosis, spreading of pesticides, or material self-assembly . In the past decades, such configuration witnessed an increased interest in the context of inkjet printing, which has overcome the usual application of printing on paper to become a cheap and versatile method for additive manufacturing, employed for flexible organic and inorganic electronics, light-emitting devices, pharmaceutical products, biomaterials, or filtration membranes …”
Section: Introductionmentioning
confidence: 99%